El mundo de Sofía : novela sobre la historia de la filosofía - Gaarder, Jostein, 1952-; Baggethun, Kirsti; Lorenzo, Asunción; Gaarder, Jostein, 1952- (Madrid : Ediciones Siruela, 2010)
The protagonists are Sophie Amundsen, a 14-year-old girl, and Alberto Knox, her philosophy teacher. The novel chronicles their metaphysical relationship as they study Western philosophy from its beginnings to the present.
Online resource; title from ePub title page (Digitalia, viewed March 25, 2016)
Keywords: Philosophy -- History -- Fiction; Didactic fiction; Electronic books